2018
DOI: 10.2217/nmt-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Age/Disease Duration Influence on Activities of Daily Living and Quality of Life After Levodopa-Carbidopa Intestinal Gel in Parkinson’s Disease

Abstract: LCIG therapy led to sustained improvements in quality of life irrespective of patient age and disease duration at baseline. Improvements in activities of daily living were observed across all subgroups, particularly in younger patients, patients with shorter disease duration and in patients with the highest baseline levodopa equivalent dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
2
14
1
1
Order By: Relevance
“…In line with this result, our study reported that the duration of off-time significantly affected patient QoL (Table 3). Interestingly, previous studies have reported inconsistent results in terms of whether age influences QoL in patients with PD [28,29]. In our study population of Japanese patients, the patient's age significantly affected QoL whereas a study conducted in Singapore showed an inconsistent result [28].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In line with this result, our study reported that the duration of off-time significantly affected patient QoL (Table 3). Interestingly, previous studies have reported inconsistent results in terms of whether age influences QoL in patients with PD [28,29]. In our study population of Japanese patients, the patient's age significantly affected QoL whereas a study conducted in Singapore showed an inconsistent result [28].…”
Section: Discussioncontrasting
confidence: 53%
“…In previous studies in Japanese and Malaysian populations, gastrointestinal disorders, such as constipation, were the commonly reported nonmotor symptoms [12,30]. In a study conducted in Italian patients with PD (n = 1072), gastrointestinal symptoms were reported by 61% of patients and worsened QOL [29]. In this JAQPAD study, apathy was associated with the worst QoL score, followed by cardiovascular symptoms, fatigue, attention/memory, and respiratory symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…Patients were also required to demonstrate a positive clinical response to LCIG administered via a temporary nasojejunal (NJ) tube prior to receiving a permanent PEG-J tube. Patients were enrolled from 75 movement disorder centers in Australia, Austria, Belgium, Bulgaria, Czech Republic, Denmark, France, Germany, Greece, Ireland, Italy, Netherlands, Norway, Romania, Slovenia, Spain, Switzerland, and the United Kingdom [13,14].…”
Section: Gloria Registrymentioning
confidence: 99%
“…Also, the percentage reductions of NMS and PDQ-8 vs BL were greater in the Italian sub-group analysis compared to the total GLORIA population even if the Italian group baseline “Off” time was lower (4.3 ± 2.7 vs 6.0 ± 3.2 h). This observation seems of interest considering that in another GLORIA sub-analysis, it was recently reported that the magnitude of QoL improvement was greater in patients with more “Off” time and larger LED dose at baseline [ 30 ]. LCIG led to significant improvements in UPDRS II and III scores, 24% and 17%, respectively, at M24.…”
Section: Discussionmentioning
confidence: 99%